IMPLEMENTASI KARAKTER PEDULI SOSIAL SIVITAS AKADEMIKA FPIPS UPI DALAM MERESPON PANDEMI CORONAVIRUS DISEASE 2019 (COVID-19) - Dimas Febriansyah Krisna Dwiputra, - (2020)
WHO categorizes Covid-19 a pandemic, that has an impact on various aspects of life. In this condition, it turns out that there are individuals who care to help other, one of them is the academic community of FPIPS UPI. Therefore, the researcher is interested in raising this issue into research that purposes to describe in-depth about the implementation of social care characters in the academic community of FPIPS UPI in responding to the Covid-19 pandemic based on a component of moral knowing, moral feeling, and moral activities. This research uses a qualitative approach with a case study strategy. While the data collection techniques through observation, documentation study, and interviews online to selected participants based on snowball sampling technique. The general result of this research is the implementation of social care characters in academic community FPIPS UPI involve three-component characters, that is knowing the good, desiring the good, and doing the good. The specific result of this research such as First, the academic community have good knowledge of social care by having knowing the moral values of social responsibility, awareness the factual problems related to Covid-19 and their impacts, have moral awareness and moral reasoning, so they deciding social care is necessary for responding to the Covid-19 pandemic. Second, the academic community shows a good sense of social care with a sense of empathy, feeling of happiness to help, the emergence of feelings confidence to be able to help, and a growing desire to continue taking social care activities. The last, the social care actions practiced by the academic community are very diverse, both in light and weight scales, which can generally be classified into four classes is sharing, donating, cooperative, and helping.